Epidemiological, clinical, biological, therapeutic and evolutionary profiles of infected diabetic foot hospitalized in the endocrinology department of Joseph Raseta Befelatanana University Hospital in Antananarivo, Madagascar - Raherison, Rija Eric; Raharinavalona, Sitraka A.; Razanamparany, Thierry; Andriamitantsoa, Tantely G. L.; Andrianasolo, Radonirina L.; Rakotomalala, Andrianirina D. P. (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic foot infection is a serious risk of amputation and death. Our study aims to describe the epidemiological, clinical, biological, therapeutic and evolutionary profiles of patients hospitalized for infected diabetic foot. Methods: This is a descriptive cross-sectional study conducted in the Endocrinology department of the Joseph Raseta Befelatanana University Hospital, Antananarivo over a period of 4 years. The diagnosis of infected diabetic foot was made according to the criteria of the French-Speaking Society of Infectious Pathology. We included all patients who had undergone bacteriological examination with antibiogram of their diabetic foot lesion. Results: Fifty patients were retained, giving a hospital prevalence of 2.84%. Their mean age was 55.50±9.63 years, the sex ratio was 0.72 and mean duration of their diabetes was 6.87±6.13 years. The majority of the lesions were post-traumatic (28%). The mean hospital length stay was 42.82±35.26 days. Infections were classified as stage 4 for 72% of the patients. The main isolated bacteria were Staphylococcus aureus (54.69%), of which 83% were sensitive to Amoxicillin-Clavulanic Acid. Seventy percent of the patients were infected with multidrug-resistant bacteria. The amputation rate was 30% and the mortality rate was 2%. Conclusions: Therapeutic education on podiatric care must be optimized. Multi-disciplinarity is essential for management. Amoxicillin-clavulanic acid should be preferred as probabilistic antibiotic therapy for diabetic foot infection in our country where bacteriological examination is often lacking.